DEVELOPMENT OF INNOVATIVE ACTIVITIES OF THE PEDAGOGUE BASED ON A CREATIVE APPROACH - O’sarov Bunyod (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article explores the development of innovative activities for pedagogues based on a creative approach. It highlights the importance of fostering creativity and innovation in educational settings and provides strategies for creating engaging and dynamic learning experiences. The article emphasizes the integration of gamification, design thinking, community engagement, multimedia, cross-curricular integration, reflection, authentic audience, global awareness, self-expression, and emerging technologies. It also emphasizes the significance of a growth mindset, collaboration, real-world problem-solving, creativity in assessment, reflection, cross-age mentorship, curiosity, flexible learning spaces, and a community of inquiry. The article concludes by emphasizing the continuous process of innovation and the cultivation of a creative mindset in pedagogues.